METODE PEMBELAJARAN CARD SORT UNTUK MENINGKATKAN HASIL BELAJAR MATERI QOLQOLAH MAPEL PAI DI SMP NEGERI 03 KUDUS JAWA TENGAH - Kholidah, Nur (Berajah Journal, 2024)
The card sort method is used to find out and ensure that students really know and understand the material being taught by pairing cards that have been made by the teacher with the topic being taught. All methods are not free from advantages and disadvantages. The card sort method also has shortcomings or weaknesses, namely that it takes up too much time so it can be said to be inefficient from a time aspect. Therefore, it is necessary for learning to be carried out using the Card Sort method so that students are able to find various authentic problems, namely problems that are in accordance with the reality of their social life. The Qur'an is a holy book that is different from the holy books of other religions, books and scriptures. It is not enough just to read the Qur'an, but to put into practice the messages contained in it. Reading the Qur'an has provisions called the science of tajwid. This research focused on qolqolah with a qualitative descriptive approach and classroom action. The data collection method was carried out using tests, observations and interviews. This research resulted in the finding that the card sort method was carried out in three stages, namely the planning/preparation stage by preparing the RPP and materials or media, the implementation stage was carried out by implementing the card sort method technique and the evaluation stage was carried out by carrying out tests or repetitions of the material being taught. The card sort method is a method that can increase student motivation and learning achievement even though it is carried out irregularly (continuously) because the card sort method is able to foster new pleasant feelings for students.